Burgerlora / Muhammad U’mair Shahrun Fahmi - Shahrun Fahmi, Muhammad U’mair (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
Take a tasteful trip through the evolution of Burgerlora, a delicious take on the classic Langit Cheese Burger. Located in the busy center of Ipoh, Perak, this restaurant faced a problem when its logo and dull packaging were inconsistent when it first opened on February 15, 2015. As a result, a comprehensive redesign project was initiated, bringing the packaging and logo into line with the genuine brand identity. The carefully created packaging and logo feature fonts that are meant to be readable from a distance in addition to reflecting the essence of the items. This redesign creates an identity that connects with the essence of the product, going beyond a simple visual makeover. The brand-new slogan, "Authenticity In Every Bite," perfectly captures Burgerlora's essence, where premium Australian meat imports serve as the foundation for this mouthwatering discovery. The understated logo design foreshadows a high-end experience, paving the way for a calculated marketing revolution. Step inside an engrossing world of commercials that have been tastefully decorated with color. Vibrant colors grab the eye and make the burger product look good, but it also tastes great, spicy, juicy, and incredibly fresh. This ad story is told through social media, periodicals, subways, and bus stops. With a new logo that draws inspiration from Pinterest boards, Burgerlora is poised to become a major player in the fast - food industry . Get ready for an extraordinary experience, as each mouthful serves as a tribute to the authenticity ingrained in Burgerlora's redesigned brand. Finally, Burgerlora invites you to get yourself ready for an incredible eating experience, where each bite serves as more than just a meal, it is a symbol of the authenticity that has been woven into the very fabric of the restaurant's redesigned identity. Embark on this flavorful journey , where every mouthful commemorates the skill and commitment that characterize Burgerlora's renewed essence.